Research of Reducing Gear Bending Stress based on Multi-parameter Optimization - Zhao Xiangfei; Cui Yan; Zhang Tianyi (Jixie chuandong)
Gear is an important part for mechanical transmission. In order to avoid the case of bending fatigue fracture during transmission,with the maximum bending stress of the tooth root as the objective function,and the tooth thickness greater than 0. 25 m and the coincidence degree greater than 2 as the constraint,the tooth profile parameters are optimized. In the case of the center distance constant,the solution is optimized by using the loop in Matlab,and then the finite element model of the gears is founded by ANSYS APDL language.The bending stress analysis is carried out in the meshing state to verify the reliability of the optimization results,which has a guiding significance to reduce the bending stress.